The Theatre of Robert Edmond Jones (Wesleyan University Press, 1977)
Robert Edmond Jones (1887-1954) spent his career as a theater set designer. He also worked on the production of early Technicolor films as a color consultant. As a stage designer, Jones is best known for his simplified sets that complemented the action of a production and his dramatic use of color in costuming and lighting. Jones became an innovative force in modern set design for the American theatre and is credited with bringing "The New Stagecraft" to the American drama. He also designed for opera and dance and was named Radio City Music Hall's first art director in 1932. This collection of essays presents a record of his innovative work and impact on the world of theatre. The volume includes contributions from collaborators. Those interested in stagecraft and the history of modern theatre will find this work a valuable illumination of the method of one of the most important figures in the history of modern theatre.